Small but mighty: Platelets as central effectors of host defense - Stocker, Thomas J.; Hellen, Ishikawa-Ankerhold; Steffen, Massberg; Christian, Schulz (Thrombosis and Haemostasis, 2017)
Platelets actively participate in inflammatory processes and drive diseases such as atherosclerosis, rheumatoid arthritis and cancer metastasis. However, platelets also have anti-inflammatory and anti-infective properties, which have received less consideration in the past. In this review, we highlight recent findings on the role of platelets in host defense and describe regulatory pathways modulating immuneresponses. Furthermore, we discuss the role of platelets for the resolution of inflammation and tissue repair. These conceptual changes contribute to our understanding of platelet biology in disease.
Keywords: Platelet immunology; Inflammation; platelet physiology; sepsis; leukocyte function / activation